SIMILARITY ANALYSIS OF GENERA AQULARIA AND GYIRINOPS BASED ON VEGETATIVE STRUCTURE FEATURE USING DIFFERENT CLUSTERING METHOD - I Gde Adi Suryawan Wangiyana (SANGKAREANG, 2019)
The purpose of this research is to analysis similarity of Aquilaria group and Gyrinops group based on several feature of vegetative organ. Member of Aquilaria Group and Gyrinops group were selecting as OTU based on their validation nomenclature from international taxonomy database. Dendrograms were constructed using MVSP version 3.1A. UPGMA Algorithm were used for clustering method. Two similarity index, Simple Matching Coefficient and Jaccard Coefficient, were used for distance measurement on dendrogram. Cophenetic correlation analysis between similarity matrix were conducted by CoStat Cohort 6. Similarity matrix based on simple matching coefficient were different from similarity matrix based on Jaccard Coefficient on the aspect of OTU pair. Simple Matching coefficient also have higher similarity index then Jaccard coefficient. Moreover, Dendrogram topology based on simple matching coefficient were different from dendrogram topology based on Jaccard coefficient on aspect of sister taxa pairing complex. Cophenetic correlation analysis confirm that distortion data between all similarity matrix were not significant. That means, dendrogram based on these clustering methods were accurate and reliable. It could be concluded that Aquilaria group and Gyrinops group has high similarity index which make them randomly clustering in the same cluster based on its vegetative character feature.